2017
DOI: 10.1002/2017pa003135
|View full text |Cite
|
Sign up to set email alerts
|

Antarctic climate, Southern Ocean circulation patterns, and deep water formation during the Eocene

Abstract: We assess early‐to‐middle Eocene seawater neodymium (Nd) isotope records from seven Southern Ocean deep‐sea drill sites to evaluate the role of Southern Ocean circulation in long‐term Cenozoic climate change. Our study sites are strategically located on either side of the Tasman Gateway and are positioned at a range of shallow (<500 m) to intermediate/deep (~1000–2500 m) paleowater depths. Unradiogenic seawater Nd isotopic compositions, reconstructed from fish teeth at intermediate/deep Indian Ocean pelagic si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 143 publications
(276 reference statements)
5
42
0
Order By: Relevance
“…Under these conditions, bottom water formation and downwelling can still occur (with or without presence of sea ice) as a result of density contrasts related to seasonal changes in surface water temperature and salinity (Huber and 620 Sloan, 2001;Otto-Bliesner et al, 2002). Moreover, stable Nd isotopic composition in EoceneOligocene sediments from Site U1356 is consistent with modern day formation of bottom water from Adélie Land, as reported by Huck et al (2017). Our evidence above points to deposition of F1 during glacial cycles under poorly-ventilated, low-625 oxygenation conditions at the water-sediment interface (Fig.…”
supporting
confidence: 77%
“…Under these conditions, bottom water formation and downwelling can still occur (with or without presence of sea ice) as a result of density contrasts related to seasonal changes in surface water temperature and salinity (Huber and 620 Sloan, 2001;Otto-Bliesner et al, 2002). Moreover, stable Nd isotopic composition in EoceneOligocene sediments from Site U1356 is consistent with modern day formation of bottom water from Adélie Land, as reported by Huck et al (2017). Our evidence above points to deposition of F1 during glacial cycles under poorly-ventilated, low-625 oxygenation conditions at the water-sediment interface (Fig.…”
supporting
confidence: 77%
“…The gradients between basins diminish during hyperthermals due to reductions or reversals in overturning circulation (e.g., Zeebe & Zachos, ) triggered by warming (Kirtland Turner et al, ; Lunt et al, ). Convergence of δ 13 C from 52 to 47.25 Ma could point to increased deep‐water exchange (bidirectional mixing) between Atlantic and Pacific well before the widening of the circum‐polar gateways ~40 Ma ago (Scher & Martin, ; Thomas et al, ) or an increase in bottom water formation around Antarctica as reported from South Ocean Nd records (Huck et al, ). A reduction in the style of communication (bidirectional to uni‐directional) after 47.25 Ma could be the result of changes in deep‐water formation regions as climate cools after the end of the EECO.…”
Section: Discussionmentioning
confidence: 96%
“…In the southwest Atlantic, at Sites 696 and 511 and the onshore Austral Basin, the effects of tectonic reorganization near the Drake Passage are expected to be potentially important. Although tectonic reconstructions for Drake Passage deepening remain ambivalent, there are no clear indications for a major reorganization in the late Eocene (e.g., Hill et al, ; Huck et al, ; Lagabrielle et al, ; Wright et al, ). We therefore ascribe enhanced bottom water flow in the southwest Atlantic to enhanced circulation of its western boundary as a likely westward propagation of the Antarctic Countercurrent.…”
Section: Discussionmentioning
confidence: 99%